Tomas used incorrectly the rule of signs, the expression should be simplified as follows:
-2.6 + (-5.4)
-2.6 -5.4 = 8
<h3>
</h3><h3>
What mistake did Tomas likely make?</h3>
Here Tomas wants to perform an addition between two numbers:
-2.6 + (-5.4)
And the outcome that Tomas gets is:
-2.6 + (-5.4) = 2.8
Here his mistake seems to bee that he thought the second number was a positive number, and he solved the operation:
-2.6 + 5.4
So, he used wrong the rule of signs.
Remember that the rule of signs says that:
(-)*(+) = (+)*(-) = (-)
Using that, we can rewrite the original expression:
-2.6 + (-5.4)
to:
-2.6 - 5.4
Solving that, we get:
-2.6 - 5.4 = -8
Which is the outcome that Tomas would have gotten if he had used correctly the rule of signs.
If you want to learn more about the rule of signs:
brainly.com/question/13333620
#SPJ1
The partial would be
40x5=200
2x5=10
210
Your just breaking them apart
Answer:
<u>The original three-digit number is 417</u>
Step-by-step explanation:
Let's find out the solution to this problem, this way:
x = the two digits that are not 7
Original number = 10x+7
The value of the shifted number = 700 + x
Difference between the shifted number and the original number = 324
Therefore, we have:
324 = (700 + x) - (10x + 7)
324 = 700 + x - 10x - 7
9x = 693 - 324 (Like terms)
9x = 369
x = 369/9
x = 41
<u>The original three-digit number is 417</u>
1. To solve this exercise, you must make a system of equations.
2. You have that f<span>our times a number minus twice another number is -8:
</span>
4x-2y=-8
3. And t<span>he sum of the two number is 19:
</span>
x+y=19
4. As you can see, you have two equations:
4x-2y=-8 (i)
x+y=19 (ii)
5. Let's clear the "x" from the equation (ii):
x=19-y
6. Now, you need to susbtitute x=19-y into the equation (i):
4x-2y=-8
4(19-y)-2y=-8
76-4y-2y=-8
76-6y=-8
-6y=-8-76
-6y=-84
y=-84/-6
y=14
7. You must susbstitute y=14 into the equation (ii) and clear "x":
x+y=19
x+14=19
x=19-14
x=5
The answer is: 5 and 14
If you would like to know the solution to the equation (x - 2) * (x + 5) = 18, you can calculate this using the following steps:
(x - 2) * (x + 5<span>) = 18
</span>x^2 + 5x - 2x - 10 = 18
x^2 + 3x - 28 = 0
(x + 7) * (x - 4) = 0
1. x = - 7
2. x = 4
The correct result would be x = - 7.